Field notes contributed by Tanya Bray, fall 1981 - Bray, Tanyaet al (1981)
Field notes were contributed by Tanya Bray and other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1981. Epson - sheet feed